Zlate ose Slovenije (Hymenoptera: Chrysididae) - Gogala, Andrej (Scopolia, 2016)
Cuckoo wasps (Chrysididae) are parasitoids or cleptoparasites of other hymenopterans. The first list of cuckoo wasps of Slovenia is presented herewith, prepared on the basis of specimens in museum collections of the Slovenian Museum of Natural History and the Notranjska Museum Postojna, published records and, in a few cases, photographs. Three species were observed at the nest of possible hosts. 84 species of cuckoo wasps have been found in the territory of Slovenia. The species Cleptes putoni Buysson had been erroneously attributed to Slovenia in the past.
Keywords: Chrysididae; cuckoo wasps; entomological species; Hymenoptera; kožokrilci; ose; Prirodoslovni muzej Slovenije; Slovenia; Slovenian Museum of Natural History; Slovenija; zlate ose; zoological collections; zoologija; zoology; zoološke zbirke; žuželke